2019
DOI: 10.15389/agrobiology.2019.4.810eng
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTS OF CHROMIUM MICROADDITIVE IN DIFFERENT DIETS FOR LAYING HENS (Gallus gallus L.) ON THE INTESTINAL DIGESTION AND CERTAIN BIOCHEMICAL BLOOD PARAMETERS

Abstract: В.И. ФИСИНИН, В.Г. ВЕРТИПРАХОВ, А.А. ГРОЗИНА, И.В. КИСЛОВА, М.В. КОЩЕЕВА Хром относится к биогенным элементам, которые необходимы для нормального развития и функционирования организма. Он регулирует синтез жиров, углеводный обмен и содержание глюкозы в крови. Известно о положительном влиянии добавок хрома при его использовании в кормлении молодняка кур. Данные о влиянии микродобавок хрома на процессы пищеварения в научной литературе малочисленны, а на животных с хронической фистулой кишечника отсутствуют. В на… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
0
0
1
Order By: Relevance
“…The results of studies on fistulated poultry showed that the chyme of the duodenum of meat chickens is characterized by high activity of digestive enzymes, which is consistent with the data from Fisinin et al (2019 ). The results obtained on the activity of digestive enzymes in parental lines of broilers ( Fisinin et al, 2017a ) indicate that hybrids (chickens) have a higher amylase activity in duodenal chyme than hens of maternal and paternal lines.…”
Section: Opinionsupporting
confidence: 88%
“…The results of studies on fistulated poultry showed that the chyme of the duodenum of meat chickens is characterized by high activity of digestive enzymes, which is consistent with the data from Fisinin et al (2019 ). The results obtained on the activity of digestive enzymes in parental lines of broilers ( Fisinin et al, 2017a ) indicate that hybrids (chickens) have a higher amylase activity in duodenal chyme than hens of maternal and paternal lines.…”
Section: Opinionsupporting
confidence: 88%
“…Хирургические операции по вживлению фистул в 12-перстную кишку были выполнены на 25 птицах в 20-25-суточном возрасте, канюлю вживляли напротив места впадения в кишечник панкреатических и желчных протоков по авторскому методу (16). В течение первых суток после операции птицу ограничивали в пище, затем кормление нормировали, следя за прохождением химуса в кишечнике.…”
unclassified